Implementation Project Based Learning - STEAM on Student’s Creative Thinking Skill in Indonesia : a Bibliometric Review - Prasetyawati, Azizah Nur; Astuti, Andari Puji (Litbang PWM Jawa Tengah, 2025)
The education reform of the 21st century has led to changes in the learning process, both in models and approaches. One such change is the integration of project-based learning with STEAM, which has been widely implemented across various fields of study and has proven effective in enhancing 21st-century skills. This study aims to explore STEAM-integrated projects that can improve the creative thinking skills of students in Indonesia. The research method used is a bibliometric review. Data were obtained from the Scopus and Google Scholar databases. A total of 107 relevant articles were found using the selected keywords. The results showed that 6 articles discussed the research topic in Indonesia. It was proven that STEAM project-based learning can enhance creative thinking skills through themes related to environmental issues. However, further implementation is needed to make students more flexible in developing project ideas.